Modulation of Kv3 potassium channels expressed in CHO cells by a nitric oxide-activated phosphatase - Moreno, Herman (Blackwell Science Inc, 2001)
1. Voltage-gated K(+) channels containing Kv3 subunits play specific roles in the repolarization of action potentials. Kv3 channels are expressed in selective populations of CNS neurons and are thought to be important in facilitating sustained and/or repetitive high frequency firing. Regulation of the activity of Kv3 channels by neurotransmitters could have profound effects on the repetitive firing characteristics of those neurons. 2. Kv3 channels are found in several neuronal populations in the CNS that express nitric oxide synthases (NOSs). We therefore investigated whether Kv3 channels are modulated by the signalling gas nitric oxide (NO). 3. We found that Kv3.1 and Kv3.2 currents are potentially suppressed by D-NONOate and other NO donors. The effects of NO on these currents are mediated by the activation of guanylyl cyclase (GC), since they are prevented by Methylene Blue, an inhibitor of GC, and by ODQ, a specific inhibitor of the soluble form of GC. Moreover, application of 8-Br-cGMP, a permeant analogue of cGMP, also blocked Kv3.1 and Kv3.2 currents. 4. KT5283, a cGMP-dependent protein kinase (PKG) blocker, prevented the inhibition of Kv3.1 and Kv3.2 currents by D-NONOate and 8-Br-cGMP. This indicates that activation of PKG as a result of the increase in intracellular cGMP levels produced by D-NONOate or 8-Br-cGMP is necessary for channel block. 5. Although the effects of NO on Kv3.1 and Kv3.2 channels require PKG activity, two observations suggest that they are not mediated by phosphorylation of channel proteins: (a) the reagents affect both Kv3.2 and Kv3.1 channels, although only Kv3.2 proteins have a putative PKA-PKG phosphorylation site, and (b) mutation of the PKA-PKG phosphorylation site in Kv3.2 does not interfere with the effects of NO or cGMP. 6. The inhibitory effects of NO and cGMP on Kv3.1 and Kv3.2 currents appear to be mediated by the activation of serine-threonine phosphatase, since they are blocked by low doses of okadaic acid. Furthermore, direct intracellular application of the catalytic subunit of protein phosphatase 2A inhibited Kv3.2 currents, indicating that activity of PKG-induced phosphatase is necessary and sufficient to inhibit these channels. 7. The results suggest that basal phosphorylation of Kv3 channel proteins is required for proper channel function. Activation of phosphatases via NO or other signals that increase cGMP might be a potent mechanism to regulate Kv3 channel activity in neurons.